2009
DOI: 10.1021/la901410h
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Changes in Stratum Corneum Lipids by Effect of Bicellar Systems

Abstract: Attenuated total reflectance-Fourier transform infrared (ATR-FTIR) spectroscopy was applied to study the effects of the bicelles formed by dimyristoyl-glycero-phosphocholine (DMPC) and dihexanoyl-glycero-phosphocholine (DHPC) in porcine stratum corneum (SC) in vitro. A comparison of skin samples treated and untreated with bicelles at different temperatures was carried out. The analysis of variations after treatment in the position of the symmetric CH2 stretching, CH2 scissoring, and CH2 rocking vibrations repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
53
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(62 citation statements)
references
References 49 publications
8
53
1
Order By: Relevance
“…The position of the band at 2851.36 ± 0.22/cm after impregnation of the porcine skin with the O/W‐macroemulsion suggested a dominating hexagonal phase, while the position of the symmetric CH 2 stretching mode at about 2852/cm after impregnation with the four multiple emulsions indicated dominating liquid disordered phases. The characteristic wave numbers of the different conformational orders of the alkyl chains of the stratum corneum lipids were reported by Rodríguez et al [24]…”
Section: Resultssupporting
confidence: 55%
“…The position of the band at 2851.36 ± 0.22/cm after impregnation of the porcine skin with the O/W‐macroemulsion suggested a dominating hexagonal phase, while the position of the symmetric CH 2 stretching mode at about 2852/cm after impregnation with the four multiple emulsions indicated dominating liquid disordered phases. The characteristic wave numbers of the different conformational orders of the alkyl chains of the stratum corneum lipids were reported by Rodríguez et al [24]…”
Section: Resultssupporting
confidence: 55%
“…Commonly investigated material systems include conjugated polymers, block copolymers, lipids, and magnetic or semiconducting materials in a wide variety of applications. [39][40][41][42][43][44][45][46] To establish and prove the feasibility of GIWAXS at BW4, we applied this technique to a variety of different samples. Here we present the sample of a thin film of the conjugated and conducting polymer poly͑3-octylthiophene͒ P3OT on top of a precleaned glass slide.…”
Section: Application Examplementioning
confidence: 99%
“…However, this was not observed, suggesting that these bicelles were not able to penetrate or disperse through the SC lipid area 40. This result was clarified by Rodriguez et al78 using attenuated total reflectance–Fourier transform infrared (ATR‐FTIR) spectroscopy. These authors reported that the application of DMPC/DHPC q = 2 bicelles caused phase transitions in the SC lipid conformation from the gel state to the liquid‐crystalline state.…”
Section: Application Of Bicelles To the Skinmentioning
confidence: 92%
“…Bicelles act to enhance penetration, causing phase transformations in lipid domains that may be relevant to skin permeation 92. As reported by Rodriguez et al,78 the phase transition of the SC lipid conformation from the gel state to the liquid‐crystalline state, which causes the fluidity of these lipids, explains the increase of TEWL in vivo. Compared to other enhancers, bicelles would have the additional advantage of not causing skin irritation 93…”
Section: Application Of Bicelles To the Skinmentioning
confidence: 92%